2022
DOI: 10.1038/s41537-022-00308-x
|View full text |Cite
|
Sign up to set email alerts
|

Language abnormalities in schizophrenia: binding core symptoms through contemporary empirical evidence

Abstract: Both the ability to speak and to infer complex linguistic messages from sounds have been claimed as uniquely human phenomena. In schizophrenia, formal thought disorder (FTD) and auditory verbal hallucinations (AVHs) are manifestations respectively relating to concrete disruptions of those abilities. From an evolutionary perspective, Crow (1997) proposed that “schizophrenia is the price that Homo sapiens pays for the faculty of language”. Epidemiological and experimental evidence points to an overlap between FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 222 publications
1
3
0
Order By: Relevance
“…First, we found that the epicenter distribution of schizophrenia is spatially correlated with a low-dimensional representation of cognitive processes, to which the greatest positive contributions are enriched at language processes. This is in line with our observation that the language region as the possible origin of neurophysiological pathology, supporting language hypothesis in schizophrenia ( 57 , 58 ). Second, we found a robust spatial concordance between the epicenter distribution of schizophrenia and gene expression profiles of cerebral cortex.…”
Section: Discussionsupporting
confidence: 92%
“…First, we found that the epicenter distribution of schizophrenia is spatially correlated with a low-dimensional representation of cognitive processes, to which the greatest positive contributions are enriched at language processes. This is in line with our observation that the language region as the possible origin of neurophysiological pathology, supporting language hypothesis in schizophrenia ( 57 , 58 ). Second, we found a robust spatial concordance between the epicenter distribution of schizophrenia and gene expression profiles of cerebral cortex.…”
Section: Discussionsupporting
confidence: 92%
“…The general idea is that Grammar in the face of SZ has a specific linguistic profile, which differs from neurotypicals' profile. Moreover, the link between SZ and language dysfunctions is supported by current findings indicating associations between FTD and structural and functional anomalies in language areas of the brain [16,17], as well as an overlap between FTD and AVH, even in early stages of SZ, with substantial shared anomalies in language areas of the brain, and gene overlap between language dysfunctions and SZ [18,19].…”
Section: Introductionsupporting
confidence: 71%
“…These symptoms can manifest in vocal features like a slower rate of speech with shorter utterances, more pauses, reduced variation in frequency or in language use, like in decreased density of ideas ( 15 ). In addition to these speech alterations, individuals with psychosis may exhibit other speech-related phenomena such as perseveration (continual involuntary repetition of a thought), neologisms (the coining or use of new words), clang associations (groupings of words that are based on similar-sounding sounds, even though the words themselves do not have any logical reason to be grouped together), and echolalia (the unsolicited repetition of utterances made by others) ( 12 , 16 ) ( Table 2 ).…”
Section: Language and Psychosismentioning
confidence: 99%